International students’ experiences of hospitality service in Malaysian research universities - Tukimin, Siti Nurhidayaah (2016)
This study aims to determine the relationship between hospitality service delivery dimensions and international students’ satisfaction where it is focuses on the services provided by faculty and hostel. This research is able to enlarge the body of knowledge in the service management by exploring the international students’ experience in the context of service delivery. The services are consists of service quality dimensions (tangible, reliability, responsiveness, assurance and empathy) and servicescape dimensions (ambient condition, space/function and sign, symbol and artifact). Quantitative method has been used to gather the data. The data collection has been done through distributing questionnaires towards international students using convenience sampling technique. The questionnaires were distributed in three Malaysian research universities in Klang Valley namely Universiti Putra Malaysia, Universiti Kebangsaan Malaysia and Universiti Malaya. A total of 400 questionnaires were distributed with 383 respondents participated in this research. The hospitality services delivery dimensions were tested for its reliability strength and the results showed that all dimensions were highly reliable. Factor analysis and multiple regressions were conducted to analyze the data and to test the hypotheses. Multiple regressions were used to achieve both first and second objectives which were to determine the relationship amongst hospitality service delivery (service quality and servicescape) and international students’ satisfaction. The regression result for faculty services showed that tangible, empathy and responsiveness dimensions of service quality were the major component that influenced the students’ satisfaction while space and function of servicescape dimensions were the major component that influenced the students’ satisfaction.